La Batteria per le Funzioni Esecutive nell’Addiction - BFE-A: un nuovo tool digitalizzato per lo screening neurocognitivo - Balconi, Michela; Losasso, Doriana; Balena, Alessandra; Crivelli, Davide (Mission - Open Access, 2023)
According to recent neurocognitive models of addictions, a vicious combination of altered executive functions (EF) and dysfunctional reward system represents a main determinant of clinical picture. Executive dysfunctions also have a great impact on worsening addiction disorders as well as on treatment outcomes. Thus, detecting executive dysfunctions with sensitive tools is crucial in order to tailor therapeutic and rehabilitative interventions to patients. We here report the testing of the Battery for Executive Functions in Addiction (BFE-A), a novel battery for EF screening.151 patients with Substance-Use Disorder and 56 health participants completed the seven digitized BFE-A subtests tapping on: learning and memory, working memory, cognitive flexibility, focused attention, attention regulation, and inhibitory control. First-level statistical analyses highlighted lower performance of the clinical sample with respect to healthy participants across all the battery subtests, though verbal memory and focused attention proved to be te most impaired functions. Regression analyses, then, revealed that longer abstinence led to greater memory performance and that a longer history of substance abuse specifically led to less efficient information-processing speed. Findings provide support to the evaluation of the BFE-A as a brief but informative screening battery, potentially complementing the diagnostic process in clinical settings.